Oral Health Status among Drug Addicts in a Selected Hospital in Dhaka City (Bangladesh Journal of Dental Research & Education, 2015)
This was a cross-sectional study on oral health status of drug addicted patients admitted in a drug abuse treatment center in Dhaka city. This study was conducted at Mukti Mental Hospital, Drug & Alcohol Treatment Center situated at Gulshan, Dhaka, Bangladesh. The study was carried out among 50 drug addicts from the month of January to June 2012. Data were collected from the patients from 21st April to 5th May 2012. The main objective of the study was to assess and investigate the oral hygiene practice and oral health status of drug abusers. Fifty drug abusers irrespective of sex and age were interviewed & their oral health status was evaluated using the World Health Organization recommended procedures for Decayed, Missing, Filled teeth and the periodontal status. Data were collected with a pretested structured questionnaire and checklist.  Dental caries was found in 92% of the drug addicts, while Missing and Filled teeth were recorded 86% and 88% of the addicts respectively.  86% of the addicts demonstrated DMFT score 1 or Higher; whereas 14% of the addicts demonstrated DMFT score 0 or were free from any form of dental decay, missing teeth or dental filling and 74% of the drug addicts had gingival inflammation and bleeding from gum, 42% had some oral mucosal lesion like apthus ulcer and candidiasis. The number of Decayed, Missing or Filled teeth increased with less frequency of daily tooth brushing and this finding was significant (p